How NFTs contribute to consumers’ purchase intention towards luxury fashion physical products - Liufang Zhang; Jiaozuo, China; Ing Grace Phang (Emerald Publishing Limited, 2024)
Purpose – This study aims to examine the impact of non-fungible tokens (NFTs’) characteristics on Chinese consumers’ purchase intention towards luxury fashion physical products. It also investigates the mediating role of perceived hedonic value and moderating role of perceived NFT–physical product fit during the buying process. Design/methodology/approach – A conceptual model combining Stimuli–Organism–Response Model and Theory of Consumption Value was established. A purposive sampling method was adopted to collect data from luxury fashion consumers aged 21–41 who lived in four Tier 1 citiesinChina. Structural equation modelling and SmartPLS 4.0 were utilized to analyse the 304 valid questionnaires collected. Findings – The study’sfindings indicate that luxury fashion NFTs with four characteristics (NFTscarcity, NFT exclusivity, NFT design aesthetic and NFT novelty) affect Chinese consumers’ purchase intention towards luxury fashion physical products positively, with perceived hedonic value mediating these relationships. Further, perceived NFT–physical product fit moderates the relationship between perceived hedonic value and purchase intention. Originality/value – This study bridges a gap in investigating the interplay between NFTs as intangible collectibles and tangible products, by stressing the significant role played by NFTs in influencing the purchase intention of luxury fashion products. This paper contributes to an understanding of consumers’ psychological responses and behaviours towards NFTs, providing a new perspective in the study of luxury fashion NFTsin the context of marketing strategy and consumption.